2011
DOI: 10.1136/bjo.2010.197426
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics and appearance of the normal optic nerve head in 6-year-old children

Abstract: The mean vertical cup/disc ratio was 0.4 in this 6-year-old sample. Planimetric optic nerve head measures and population prevalence findings for optic disc signs in this population could be regarded as normative data for ophthalmologists in clinical settings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 27 publications
0
8
2
Order By: Relevance
“…Vitreous humour • Vitreous liquefaction [10][11][12] • Posterior vitreous detachment 10,13,14 12.5% (myopia < −8.25 D) 13 Optic disc • Tilt and rotation [15][16][17][18] • Myopic conus [19][20][21] • Peri-papillary atrophy [19][20][21][22][23] 33.8% (myopia < −8.00 D) 24 Peripheral retina • Lattice degeneration [25][26][27] • White without pressure 26,28 • Peripheral retinal degeneration [25][26][27]29,30 16.9% (myopia < −6.00 D) 26 Choroid/retinal pigment epithelium/sclera/retina…”
Section: Condition Prevalencementioning
confidence: 99%
See 2 more Smart Citations
“…Vitreous humour • Vitreous liquefaction [10][11][12] • Posterior vitreous detachment 10,13,14 12.5% (myopia < −8.25 D) 13 Optic disc • Tilt and rotation [15][16][17][18] • Myopic conus [19][20][21] • Peri-papillary atrophy [19][20][21][22][23] 33.8% (myopia < −8.00 D) 24 Peripheral retina • Lattice degeneration [25][26][27] • White without pressure 26,28 • Peripheral retinal degeneration [25][26][27]29,30 16.9% (myopia < −6.00 D) 26 Choroid/retinal pigment epithelium/sclera/retina…”
Section: Condition Prevalencementioning
confidence: 99%
“…21 A tilted optic disc is one of the most commonly associated features of high myopia and is observed in adults as well as children, with the earliest observed in children as young as six years old. 15 The reported prevalence varies in children and adults, with one study reporting 75 per cent in high myopic adults 83 whereas a second study reported 37 per cent prevalence in moderately myopic children. 77 Visual acuity may not be affected with the presence of optic disc tilt alone.…”
Section: Condition Prevalencementioning
confidence: 99%
See 1 more Smart Citation
“…They found similar results to Mansour. In another photographic study, Samarawickrama et al14 documented planimetric measures of normal optic nerve head parameters in a populationbased study of 6-year-old children and reported smaller optic disc sizes. This discrepancy may be due to the different image analysis techniques.…”
mentioning
confidence: 99%
“…[2225] Some studies investigating disc parameters only used vertical CDR for this reason. [26, 27] Average CDR was defined as the mean of vertical and horizontal CDR in this study. Since average CDR includes horizontal CDR which is not variable in terms of other ocular parameters, this could be the reason why our data only showed significance with vertical CDR, and not with average CDR in some analyses.…”
Section: Discussionmentioning
confidence: 99%